RESEARCH ON THE INFLUENCE OF A MAGNETIC FIELD WITH VARIABLE INDUCTION ALONG THE LENGTH OF THE FLOW AXIS ON THE COMPOSITION AND PROPERTIES OF WATER FOR HEATING NETWORKS - DUSHENKO, OLEKSANDR; TKACHUK, VITALIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Poor-quality water treatment for boilers and contaminants present in untreated water lead to a number of problems: large colloidal and mechanical contaminants in the form of scale, rust, clay or sand quickly clog pipes, significantly reducing their internal diameter. This leads to failure of shut-off valves and pumping equipment: hardness salts and other poorly soluble salts (carbonates, magnesium and calcium sulfates, silicates, various copper and manganese compounds) settle, forming a crust on the metal walls of the equipment, which reduces its heat transfer. The main directions of building the design of electromagnetic and magnetic devices for the influence of a magnetic field on water and water systems are considered. From the analysis of sources, it was established that the magnetic field, which can be created by electromagnets or permanent magnets, significantly affects the change in the properties and composition of water, and equipment and devices must have a variable magnetic field induction along the passage of water, which is achieved by certain distances between the magnets. The study of the performance of the proposed design of equipment for water preparation for heating networks, with multi-cyclic time-dependent magnetic field effects on water, is an urgent scientific and technical task. An experimental installation of cyclic magnetic effects on water has been developed, which enhances the effect of breaking hydrogen bonds in water molecules, oxidation of iron and calcium ions, and increasing the pH index. The study of the effect of a magnetic field on water hardness and structural state has been conducted. Studies of crystal-optical analysis of the structure of a dried water drop after treatment with a magnetic field have confirmed that a more structured state is obtained and the surface tension coefficient of water decreases, and the pH index increases. A study was also conducted on thermostatic measurements of the boiling point of distilled water.